EPID-09. THE ROLE OF GENDER PHENOTYPE IN PAEDIATRIC CNS TUMOUR INCIDENCE AND SURVIVAL. (5th November 2018) - Mathew, Ryan; Solanki, Sandeep; Cheong Soon, Wai; Hayes, Josie; Kapetanstrataki, Melpo; Fleming, Sarah; Parslow, Roger; Picton, Sue; Chumas, Paul
Abstract: INTRODUCTION: The impact of patient gender in germinomas and medulloblastomas is a well-documented factor influencing incidence and outcome of these tumours, which may be due to differential susceptibility to tumourogenesis and treatment response between the genders. The role of gender phenotype in other paediatric CNS tumours is not as distinct. METHODS: The Surveillance Epidemiology and End Result (SEER) registry (covering 28% of US patients) between 2000–11 was used to collect age-adjusted incidence and overall survival (OS) rates for common paediatric (<=19 years) CNS tumours - pilocytic astrocytoma (PA), anaplastic astrocytoma (AA), glioblastoma multiforme (GBM), medulloblastoma (MB), sPNET, ependymoma (EP), germinoma (G) and pleomorphic xanthoastrocytoma (PXA). Patients with histologically confirmed, ICD-03 coded, first tumours, were included. Mortality was defined as any cause of death between 1–60 months of diagnosis. Results were statistically analysed by Incidence Rate Ratio (IRR), Kaplan-Meier and Log Rank (Cox Proportional Regression Hazard) Testing (p<0.05). RESULTS: A total of 5712 cases were registered (3169 male, 2543 female). Males exhibited the highest incidence of all tumours except PA. Comparing the opposite gender at the same ages, 1- and 5-year OS was better in males aged 3–4 years for MB, sPNETs, GBM and AA, females aged 0–19 years for MB, females aged 0–2 years and 15–19 years for AA; 5-year OS was better in females aged 0–2 years with EP; 1-year OS was better in males aged 3–4 year with AA. CONCLUSION: Population-based registries such as SEER can deliver credible data and minimise bias. Gender differences in both incidence and OS for different paediatric CNS tumours provide useful prognostic information for clinicians. Further research into possible hormonal and epigenetic differences may provide targets unique to males or females to tailor therapy.